"Missed nursing care" in health promotion: Raising awareness. (20th May 2020) - Lopez‐Dicastillo, Olga; Zabaleta‐del‐Olmo, Edurne; Mujika, Agurtzane; Antoñanzas‐Baztán, Elena; Hernantes, Naia; Pumar‐Méndez, María‐J
Abstract: Aim(s): This commentary aims to raise awareness of the possible causes of "missed nursing care" in health promotion and to propose possible solutions. Background: Although health promotion is an essential function of nursing practice, "missed nursing care" has been scarcely studied in this area. It is crucial to know both its causes and possible strategies to prevent it. Evaluation: We used evidence to identify possible causes of "missed nursing care" in health promotion, and we classified them into categories. We suggested the concept of capacity building to address its underlying causes. Key issue(s): Four main factors are involved in "missed nursing care" in health promotion, that is intrapersonal, interpersonal, organisational and cultural. Capacity building, including the development of knowledge, skills, commitment, structures, systems and leadership, could reduce missed care. Conclusion(s): "Missed nursing care" in health promotion is complex and is multifactorial in its origins. Capacity building could be a way to address its causes. Implications for Nursing Management: Nursing care in health promotion is paramount and a long‐term investment that can contribute to the sustainability of the health system. Organisations and managers could view capacity building processes as a tool to prevent "missed nursing care" in health promotion.